2018
DOI: 10.1080/13880209.2018.1457061
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide from Rhodobacter sphaeroides (TLR4 antagonist) attenuates hypersensitivity and modulates nociceptive factors

Abstract: Context: Accumulating evidence has demonstrated that Toll-like receptors (TLRs), especially TLR4 localized on microglia/macrophages, may play a significant role in nociception.Objective: We examine the role of TLR4 in a neuropathic pain model. Using behavioural/biochemical methods, we examined the influence of TLR4 antagonist on levels of hypersensitivity and nociceptive factors whose contribution to neuropathy development has been confirmed.Materials and methods: Behavioural (von Frey’s/cold plate) tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 100 publications
(110 reference statements)
3
9
1
Order By: Relevance
“…Furthermore, Shepherd et al (2018) showed that the angiotensin II receptor (AT2R) antagonist reduces neuropathic pain by blocking the downstream signalling of AT2R in infiltrating peripheral macrophages, as sensory neurons lack expression of this receptor. Blocking of macrophage activation using TLR antagonists (Jurga et al, 2018) and inhibitors of p38 MAPK/MMP9 (Hutchinson et al, 2008;Mika et al, 2007), PI3K and NF-kB (Popiolek-Barczyk et al, 2015) has analgesic effects in various models of neuropathic pain, consistent with our proposed mechanism of action.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, Shepherd et al (2018) showed that the angiotensin II receptor (AT2R) antagonist reduces neuropathic pain by blocking the downstream signalling of AT2R in infiltrating peripheral macrophages, as sensory neurons lack expression of this receptor. Blocking of macrophage activation using TLR antagonists (Jurga et al, 2018) and inhibitors of p38 MAPK/MMP9 (Hutchinson et al, 2008;Mika et al, 2007), PI3K and NF-kB (Popiolek-Barczyk et al, 2015) has analgesic effects in various models of neuropathic pain, consistent with our proposed mechanism of action.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, LPS was utilized as an agent to induce a pro-inflammatory state. It was demonstrated that the expression of TLR4 and NF-κB, and the secretion of IL-6 and TNF-α was significantly induced by treatment with LPS, which was consistent with the LPS-induced pro-inflammatory states demonstrated in previous studies ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 90%
“…RS-LPS produced no significant effects on the NF-κB nuclear translocation in the CVOs. Studies have revealed that RS-LPS acts a TLR4 antagonist with analgesic properties in a rat neuropathic model, modulating the release of cytokines [42]. Nonetheless, our results suggest that the existing basal immune activation, evaluated through NF-κB nuclear translocation, in the CVOs was not diminished by the presence of RS-LPS.…”
Section: Discussioncontrasting
confidence: 48%